Accuracy of Pediatric Appendicitis Score - Fadhle, Muhamed Jassim (AL-Kindy College Medical Journal, 2025)
Background: Acute appendicitis is a common surgical problem in childhood, and its prompt diagnosis is an important issue to avoid complications and decrease the negative appendectomy rate. Pediatric appendicitis score (PAS) is one tool developed to help in making decisions during the evaluation of patients with suspected acute appendicitis.Objectives: to evaluate the accuracy of PAS in diagnosing acute appendicitis in children.Subjects and Methods: A retrospective study included patients who underwent appendectomy for acute appendicitis over a period of two years. Patients were divided into two groups, positive and negative appendectomy groups. PAS was calculated for every patient, and score accuracy for every cutoff point was measured. A receiver operating characteristic curve was constructed to define the best score performance.Results: A total of 436 patients were included in the study, 374 (85.8%) patients with proved positive appendectomy. The mean PAS in the positive and negative appendectomy groups was (7.3) and (4.2) respectively, (P-value=0.001). All PAS variables were significantly more in the positive appendectomy group, except for anorexia (P-value=0.71), nausea/vomiting (P-value=0.075), and fever (P-value=0.518). The best score performance was at cutoff point 6 with a sensitivity, specificity, and accuracy of 91.71%, 87.10%, and 91.06%, respectively.Conclusions: PAS is a simple tool that can be used during the evaluation of abdominal pain in children with good diagnostic accuracy. At a score < 4, acute appendicitis could be excluded with a low missed appendicitis rate, and a score ≥ 6 could support the diagnosis of acute appendicitis with a low negative appendectomy rate.